The cradle in the grave [large type] - Hannah, Sophie, 1971- (Thorndike Press large print basic series., 2012)
TV producer Fliss Benson receives an anonymous card at work, with sixteen numbers arranged in rows of four - numbers that mean nothing to her. On the same day, Fliss finds out she'll be working on a documentary about three crib death mothers wrongly accused of murder. All three women are now free, and the doctor who testified against them is under investigation. For reasons she's never shared, this is the last project Fliss wants to be working on. Then one of the mothers is found dead, and in her pocket is a card . . .